Subinvolution of the placental site as the cause of hysterectomy in young woman. Issue 2 (8th February 2021) - Triantafyllidou, Olga; Kastora, Stavroula; Messini, Irini; Kalampokis, Dimitrios
Abstract : Subinvolution of placental sites (SPSs) is a rare but severe cause of secondary postpartum haemorrhage (PPH). SPS is characterised by the abnormal persistence of large, dilated, superficially modified spiral arteries in the absence of retained products of conception. It is an important cause of morbidity and mortality of young women. In this study, we present a case of secondary PPH in a young woman after uncomplicated caesarean delivery who was deemed clinically unstable, and finally, underwent emergent total abdominal hysterectomy. We reviewed the literature with an emphasis on the pathophysiology of this situation. Treatment of patients with SPS includes conservative medical therapy, hysterectomy and fertility-sparing percutaneous embolotherapy.